THE NATIONAL - CULTURAL FEATURES OF THE MODERN MEDIA LANGUAGE - Sobirovna, Qunduz Mustaqimova (International Journal of Psychosocial Rehabilitation, 2020)
any advertising is a means of conveying information to the listener. So, the primary and main element of advertising is the language. The text of advertising has a number of features that are different from other types of street advertising language (captions, slogans, posters).